STUDY OF THE MENTAL REPRESENTATION OF THE ENVIRONMENT IN EPILEPTIC PATIENTS - BAKOU NIANGORAN, Francois; KPI-N’DIH Annabelle; ADOU Kobenan Fieni; BA. A. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: The search for possible topographical disorientation in epileptic patients was carried out with the aim of better understanding the behavior of these patients and optimizing their neuropsychological accompaniment. Method: forty-five (45) patients suffering from generalized epilepsy after having traveled a loop, had to draw on a square sheet of blank standard A4 white paper, a free plan of the previously traveled route. We counted and compared the number of benchmarks, of change of orientations, to those of the healthy control subjects. Results: Epileptic patients significantly (F (1.46) = 22.21, p = 0.00002) have fewer decision markers than control subjects. They were significantly (F (1.46) = 11.74, p = 0.00130) more errors than the healthy control subjects in the number of changes of orientation. Conclusion: Thus, we can conclude that epileptic patients are deficient in allocentrated representations of their environment. They can therefore have topographical disorientations. Patients and parents should be informed of these disorders for better management.